Chronic hiccups: an underestimated problem - Kohse, Eva K.; Hollmann, Markus W.; Bardenheuer, Hubert J.; Keßler, Jens (Anesthesia & analgesia, 2017)
Persistent singultus, hiccupping that lasts for longer than 48 hours, can have a tremendous impact on a patient’s quality of life. Although involved neurologic structures have been identified, the function of hiccups remains unclear—they have been controversially interpreted as a primitive reflex preventing extent swallowing of amniotic fluid in utero, an archaic gill ventilation pattern, or a fetus’ preparation for independent breathing. Persistent singultus often presents as a symptom for various diseases, most commonly illnesses of the central nervous system or gastrointestinal tract; they can also be evoked by a variety of pharmacological agents. It is often impossible to define a singular cause. A wide range of treatment attempts, pharmacological and nonpharmacological, have been concerted to this date; however, chlorpromazine remains the only Food and Drug Administration-approved drug in this context. Large-scale studies on efficacy and tolerance of other therapeutic strategies are lacking. Gabapentin, baclofen, and metoclopramide have been reported to accomplish promising results in reports on the therapy of persistent singultus; they may also be effective when given in combination with other drugs, eg, proton pump inhibitors, or as conjoined therapy. As another approach of note, acupuncture treatment was able to abolish hiccups in a number of studies. When managing hiccup patients within the clinical routine, it is of importance to conduct a comprehensive and effective diagnostic workup; a well-functioning interdisciplinary team is needed to address possible causes for the symptom. Persistent singultus is a medical problem not to be underestimated; more research on options for effective treatment would be greatly needed.